Determinan kelelahan kerja ditinjau dari beban kerja dan suhu pada pekerja konveksi - Andita Yuan Sabina; Wartini Wartini; Nur Ani; Syefira Ayudia Johar (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Sinta Pertiwi Klaten Limited Liability Company is a garment manufacturing company with a majority of female workers. Based on data from a preliminary survey of 30 tailors, it was found that the most frequently complained about occupational health and safety issue was fatigue due to high workloads. Environmental factors, such as temperatures above 30°C, can exacerbate fatigue and increase the risk of workplace accidents. Purpose: To analyze the relationship between workload and environmental temperature with fatigue in garment workers. Method: This study was conducted at Sinta Pertiwi Klaten Limited Liability Company using an analytical observational method with a cross-sectional design. Simple random sampling was used, with a population of 259 tailors using the Slovin formula, resulting in 157 female workers. NASA-TLX and IFRC questionnaires were distributed for data collection, and an Area Heat Stress Monitor was used to measure room temperature. Analysis used the Spearman Rank and Mann-Whitney tests with a 95% confidence level. Results: Most workers had a high workload (131 respondents) (83.4%), a work environment that met the NAB (Natural Temperature Limit) of <30°C (129 respondents) (82.2%), and a high level of work fatigue (91 respondents) (58.0%). Bivariate analysis showed a correlation between workload and fatigue (p = 0.000) and no correlation between work environment and work-related fatigue (p = 0.090). Conclusion: Workload due to high work target demands significantly influenced work fatigue compared to workplace temperature due to the respondents' young and productive age and short tenure. Suggestion: Workers are advised to stretch their muscles during breaks to help reduce work fatigue, improve blood circulation, and relax tense muscles due to repetitive work. They should also pay attention to the timing of work temperature measurements. Keywords: Garment Workers; Workload; Work Environment Temperature; Work Fatigue.